Предмет: Алгебра, автор: svetka1574

Найти значение выражению:
1/(2+корень из3) + 1/(2-корень из3)

Ответы

Автор ответа: andreevnaelina
9

 \frac{1}{2 +  \sqrt{3} }  +  \frac{1}{2 -  \sqrt{3} }  =  \\  \frac{1(2 -  \sqrt{3}) }{(2 +  \sqrt{3})(2 -  \sqrt{3})  }  +  \frac{1( 2 +  \sqrt{3}) }{(2 -  \sqrt{3})(2 +  \sqrt{3})  }  = \\  \frac{(2 -  \sqrt{3}) + (2 +  \sqrt{3})  }{4 - 3}  =  \\  \frac{2 -  \sqrt{3}  + 2 +  \sqrt{3} }{1}  =   \frac{4}{1}  = 4
Ответ:4
Похожие вопросы
Предмет: Химия, автор: ayja227
Предмет: Алгебра, автор: Адама